A highly selective and sensitive fluorescent probe for thiols based on a benzothiazole derivative. Issue 38 (5th September 2016) - Feng, Suxiang; li, Xian; Ma, Qiujuan; Liang, Beibei; Ma, Zhuoyi
Abstract : In this work, a selective turn-on fluorescent probe1 for detecting biological thiols was designed and synthesized based on modulation of the excited-state intramolecular proton transfer (ESIPT) process of 2-(2′-hydroxy-4′-diethylaminophenyl)benzothiazole. Abstract : In this work, a selective turn-on fluorescent probe1 for detecting biological thiols was designed and synthesized based on modulation of the excited-state intramolecular proton transfer (ESIPT) process of 2-(2′-hydroxy-4′-diethylaminophenyl)benzothiazole. In the absence of Cys or GSH, probe1 exhibits weak fluorescence because of the strong quenching effect of the nitro group. Upon the addition of Cys or GSH in neutral solution containing cetyltrimethylammonium bromide micelles, the dinitrophenyl group of the probe is removed via the thiolysis of dinitrophenyl ether, thereby retrieving the ESIPT process of 2-(2′-hydroxy-4′-diethylaminophenyl)benzothiazole, which results in a fluorescence enhancement at 423 nm. The probe exhibited high sensitivity towards thiols including cysteine and glutathione, with a detection limit of 8.4 × 10 −8 M for cysteine and 8.0 × 10 −9 M for glutathione. Moreover, the probe has been successfully applied to the confocal imaging of biothiols in HepG2 cells with low cell toxicity. All of these good properties prove that it can be used to monitor thiols in living cells and as a good fluorescent probe for the selective detection of thiols.